Implementation of the Entrepreneurship Program in Preparing Students Become Entrepreneurs - Sriwahyuni, Eci; Rahmadoni, Jefril; Istikomah, Istikomah; Onia, Saifaldin Idris; Mustamin, Abdul Aziz bin; Khatimah, Husnil; Asvio, Nova (Yayasan Sembilan Pemuda Indonesia, 2023)
The high unemployment rate is due to the large number of high school graduates who do not continue their education to the tertiary level and most graduates are unable to compete for jobs. Therefore, every level of education needs to implement an entrepreneurship program to prepare students to become future entrepreneurs. This research is a literature study using the systematic literature review (SLR) method which consists of 6 stages: planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection, and data analysis. This research aims to find out the reasons for implementing the entrepreneurship program, the types of entrepreneurship programs, and the obstacles encountered in implementing the entrepreneurship program. The results of the data analysis show that the high unemployment rate and the desire to advance the economic sector are the main reasons for implementing entrepreneurship programs in schools. Broadly speaking, there are two ways to implement the entrepreneurship program in schools: first through entrepreneurship education that is integrated with subjects, extracurricular activities, and learning entrepreneurial practices, and second by holding various forms of life skills training. There are several obstacles encountered in implementing the entrepreneurship program in schools, including the mindset of students who are less developed, lack of creativity, inadequate infrastructure, and relatively short implementation time to provide less than optimal results.